2015
DOI: 10.3390/s150101022
|View full text |Cite
|
Sign up to set email alerts
|

Depth Camera-Based 3D Hand Gesture Controls with Immersive Tactile Feedback for Natural Mid-Air Gesture Interactions

Abstract: Vision-based hand gesture interactions are natural and intuitive when interacting with computers, since we naturally exploit gestures to communicate with other people. However, it is agreed that users suffer from discomfort and fatigue when using gesture-controlled interfaces, due to the lack of physical feedback. To solve the problem, we propose a novel complete solution of a hand gesture control system employing immersive tactile feedback to the user's hand. For this goal, we first developed a fast and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…We thus study the augmentation or combination of tactile input with other interaction paradigms to address its limits. In the past, tactile input has been combined with spatially aware tangible devices [SBD12, SvZP∗16, BIAI17a], mid‐air gestures [KKC∗15], and pressure input (e.g., [BH09, HL12, CDVB17]) to offer more interaction possibilities. While these techniques have been positively evaluated, most of them rely on custom‐made sensing units which limit their adoption.…”
Section: Introductionmentioning
confidence: 99%
“…We thus study the augmentation or combination of tactile input with other interaction paradigms to address its limits. In the past, tactile input has been combined with spatially aware tangible devices [SBD12, SvZP∗16, BIAI17a], mid‐air gestures [KKC∗15], and pressure input (e.g., [BH09, HL12, CDVB17]) to offer more interaction possibilities. While these techniques have been positively evaluated, most of them rely on custom‐made sensing units which limit their adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that haptic feedback has the potential to improve mid-air gestural interaction [8]. In this paper, we focus our research on the localisation of virtual widgets that are reachable by hands.…”
Section: B! Haptic Feedback For Mid-air Gesturesmentioning
confidence: 99%
“…Using piezoelectric actuators, Kim et al provided participants with haptic feedbacks to inform them of the start, the end and the recognition states of a gesture [8]. Comparing with a situation where no feedback was provided, they showed that haptic feedback increased the accuracy and reduced the trajectory length of the gesture, and potentially users' fatigue.…”
Section: B! Haptic Feedback For Mid-air Gesturesmentioning
confidence: 99%
See 1 more Smart Citation
“…These technologies include cameras and computer vision and room-based or built-in sensors such as cameras [6], PointGrab [7], laptops [8], smartphones [9,10], GPS [11], vision-based [12], and accelerometers [13,14], as well as sensors worn on the human body-such as rings [15], armbands [16], and wristbands [17,18]. However, they have drawbacks.…”
Section: Device-based Gesture Recognition Systemsmentioning
confidence: 99%